Relationship between depression and quality of life in patients with chronic diseases of a level I hospital in Lima East - Roque Afray, Missael Gabriel (2018)
The objective of this research is to analyze the relationship between depression and quality of life in patients with chronic diseases of a Level I Hospital in East Lima. The present study is design, not Experimental, cross-sectional and correlational type. The instruments used for the measurement were: the Health Status Questionnaire SF36, which contains eight dimensions, and the Hamilton Depression Scale. The sample consisted of 61 patients with chronic diseases, of both sexes and with ages between 20 and 80 years. The results showed a highly significant inverse relationship between depression and the eight dimensions of quality of life, obtaining physical function (rho = -.331; p <0.01), physical role (rho = -.407; p <0.01), body pain (rho = -.448; p <0.01), general health (rho = -.467; p <0.01), emotional role (rho = -.518; p <0.01), social function (rho = -.537) ; p <0.01), vitality (rho = -.637; p<0.01) and mental health (rho = -.566; p <0.01). Therefore, it is concluded that the higher the levels of depression, the lower the quality of life in patients with chronic diseases in a Level 1 hospital in Lima East.